Inhibition of sphingomyelin synthase 2 relieves hypoxia-induced cardiomyocyte injury by reinforcing Nrf2/ARE activation via modulation of GSK-3β. (May 2021) - Jin, Aiping; Cheng, Haijuan; Xia, Lina; Ye, Sha; Yang, Cuiling
Sphingomyelin synthase 2 (SMS2) is a vital contributor to tissue injury and affects various pathological processes. However, whether SMS2 participates in the modulation of cardiac injury in myocardial infarction has not been determined. This study aimed to evaluate the potential role of SMS2 in the regulation of cardiomyocyte injury induced by hypoxia, an in vitro model for studying myocardial infarction. Our data revealed that SMS2 expression was significantly upregulated in cardiomyocytes in response to hypoxia. Loss-of-function experiments revealed that knockdown of SMS2 markedly restored the viability of cardiomyocytes impaired by hypoxia, and attenuated hypoxia-evoked apoptosis and reactive oxygen species (ROS) generation. In contrast, cardiomyocytes that highly expressed SMS2 were more sensitive to hypoxia-induced injury. Moreover, SMS2 deficiency enhanced the activation of nuclear factor erythroid 2-related factor 2 (Nrf2) signaling through inactivation of glycogen synthase kinase-3β. Notably, suppression of Nrf2 markedly abrogated SMS2 knockdown-mediated cardioprotective effects on hypoxia-exposed cardiomyocytes. Our results illustrate that downregulation of SMS2 exerts a cardioprotective function by protecting cardiomyocytes from hypoxia-induced apoptosis and oxidative stress through enhancement of Nrf2 activation. Our study indicates a potential role of SMS2 in the modulation of cardiac injury, which may contribute to the progression of myocardial infarction.